Prosthetic Rehabilitation of a Patient with Symptoms of Iron Deficiency Anaemia in association with Fraser’s Syndrome – A Case Report (Indian Journal of Forensic Medicine & Toxicology, 2020)
About a quarter of the population in the world is affected with Anaemia and deficiency of iron is one ofthe major causes. Associated symptoms are long term fatigue, cognitive function which shows impairment,and decreased well-being. “Fraser syndrome” can be described as rare, genetically inherited disorder. It ismanifested as Crytophthalmos, Syndactyly along with Enamel Hypoplasia because of which the patient isreferred to a dentist. The following report presents the report of a male patient who had symptoms of irondeficiency anaemia and also showed signs & symptoms of Fraser’s Syndrome. Proper knowledge regardingFraser’s syndrome and iron deficiency anaemia is imperative to plan an oral rehabilitation treatment protocolfor such patients.
Keywords: Iron Deficiency Anaemia, Fraser’s syndrome, Enamel Hypoplasia, Occular Prosthesis.